Determinan Audit Delay pada Perusahaan Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia Periode 2017-2020 - Amelia Yastari; Nelvirita Nelvirita (Jurnal Eksplorasi Akuntansi, 2023)
This study is a quantitative study that aims to obtain empirical evidence regarding the effect of financial distress, internal control system, audit tenure and the complexity of the company's operations on audit delay in property and real estate companies. The population in this study are property and real estate companies listed on the Indonesia Stock Exchange for the period 2017-2020 for 4 years. This study uses purposive sampling method in selecting the sample, with a total sample of 152 samples. The data type for this study is secondary data obtained from the Indonesia Stock Exchange in the form of an annual report. Analysis of the data used is multiple regression analysis. The results showed that financial distress and the complexity of the company's operations have no significant effect on audit delay, the internal control system has a negative and significant effect on audit delay, while tenure audits have a positive and significant effect on audit delay.